Modeling the Chronotropic Effect of Isoprenaline on Rabbit Sinoatrial Node - Zhang, Henggui; Butters, Timothy; Adeniran, Ismail; Higham, Jonathan; Holden, Arun; Boyett, Mark R.; Hancox, Jules C. (Frontiers in Physiology, 2012)
Introduction: β-adrenergic stimulation increases the heart rate by accelerating the electrical activity of the pacemaker of the heart, the sinoatrial node (SAN). Ionic mechanisms underlying the actions of β-adrenergic stimulation are not yet fully understood. Isoprenaline (ISO), a β-adrenoceptor agonist, shifts voltage-dependent If activation to more positive potentials resulting in an increase of If, which has been suggested to be the main mechanism underlying the effect of β-adrenergic stimulation. However, ISO has been found to increase the firing rate of rabbit SAN cells when If is blocked. ISO also increases ICaL, Ist, IKr and IKs; and shifts the activation of IKr to more negative potentials and increases the rate of its deactivation. ISO has also been reported to increase the intracellular Ca2+ transient, which can contribute to chronotropy by modulating the “Ca2+ clock”. The aim of this study was to analyse the ionic mechanisms underlying the positive chronotropy of β-adrenergic stimulation using two distinct and well established computational models. Methods and results: We modified the Boyett et al. (2001) and Kurata et al. (2008) models of electrical activity for the central and peripheral rabbit SAN cells by incorporating equations for the known dose-dependent actions of ISO on various ionic channel currents (ICaL, Ist, IKr and IKs), kinetics of IKr and If, and the intracellular Ca2+ transient. These equations were constructed from experimental data. To investigate the ionic basis of the effects of ISO, we simulated the chronotropic effect of a range of ISO concentrations when ISO exerted all its actions or just a subset of them. Conclusions: In both the Boyett et al. and Kurata et al. SAN models, the chronotropic effect of ISO was found to result from an integrated action of ISO on ICaL, If, Ist, IKr and IKs, among which an increase in the rate of deactivation of IKr plays a prominent role, though the effect of ISO on If and [Ca]i also plays a role.